Детермінування та особливості розвитку неперервної педагогічної освіти на початку ХХІ ст. у сучасному освітньому просторі - Наталія Мукан; Олена Мукан; Катерина Істоміна (Pavlo Tychyna Uman State Pedagogical University, 2014)
У статті досліджуються основні тенденції розвитку неперервної педагогічної освіти у світовому освітньому просторі на прикладі освітніх систем Великої Британії, Канади, Сполучених штатів Америки. Охарактеризовано питання детермінації даного поняття; з'ясовано зміст неперервної професійної освіти, а також визначено основні підходи, принципи і методи розвитку неперервної педагогічної освіти в сучасних освітніх системах. В статье исследуются основные тенденции развития непрерывного педагогического образования в мировом образовательном пространстве на примере образовательных систем Великобритании, Канады, Соединенных Штатов Америки. Охарактеризованы вопросы детерминации данного понятия; раскрыто содержание непрерывного профессионального образования, а также определены основные подходы, принципы и методы развития непрерывного педагогического образования в современных образовательных системах. The major purpose for the given research is to investigate the concept of the continuous pedagogical training. The constant renewal of the already mastered knowledge and skills is the key to the future success of humankind in the XXI c. Professional development of the personnel of the education sphere is especially important because the result of their work serves as the foundation for the creation of the strong education framework for the future generations. In these circumstances, the concept of the continuous pedagogical education is particularly important. The article deals with the major tendencies of the continuous pedagogical training in the global educational domain on the basis of educational systems in Great Britain, Canada, and the USA. The given paper represents the thorough investigation of the educational system advancement on the example of the well-developed countries such as Great Britain, Canada, and the USA, which helps to enhance the efficiency of the continuous pedagogical training in Ukraine. The issue of the concept's determination is discussed; the content of the continuous pedagogical training is analyzed; the basic approaches, principles, and methods of continuous pedagogical training in modern educational systems are investigated.  So, as our study shows, there are different approaches to the interpretation of the continuous teachers' education concept based on the consideration of the education features of the country and the general trends in the international education area. The main goal of the continuous pedagogical education in the developed English-speaking countries is to provide conditions for the implementation of the continuous professional development of teachers aimed at providing professional, spiritual and physical development of the teacher who is directly considered to be the creator of the educational space in the XXI c., in which the ideological principles of teaching and cognitive activity are implemented.